38th AIAA Thermophysics Conference 2005
DOI: 10.2514/6.2005-4816
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Aerothermodynamic Environment of the Huygens Probe

Abstract: An investigation of the aerothermodynamic environment of the Huygens entry probe has been conducted. A Monte Carlo simulation of the trajectory of the probe during entry into Titan's atmosphere was performed to identify a worst-case heating rate trajectory. Flowfield and radiation transport computations were performed at points along this trajectory to obtain convective and radiative heat-transfer distributions on the probe's heat shield. This investigation identified important physical and numerical factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…The flowfield solutions obtained with the VSL method developed for this study were found to compare well with the Navier-Stokes solutions of previous studies 1 . Figure 1 presents the temperature profiles for the three trajectory points.…”
Section: The Viscous Shock-layer Stagnation Line Flowfieldsupporting
confidence: 65%
See 4 more Smart Citations
“…The flowfield solutions obtained with the VSL method developed for this study were found to compare well with the Navier-Stokes solutions of previous studies 1 . Figure 1 presents the temperature profiles for the three trajectory points.…”
Section: The Viscous Shock-layer Stagnation Line Flowfieldsupporting
confidence: 65%
“…Only the stagnation line flowfield was considered in the present study, although the same method may be used to obtain solutions downstream of the stagnation line. Chemical nonequilibrium was treated following the work of shown to give good agreement with the shock standoff and convective heating predicted by previous analyses 1 . A constant wall temperature of 2000 K was assumed for all cases and a wall emissivity of 0.9 was used for the radiation coupling calculation.…”
Section: The Viscous Shock-layer Stagnation Line Flowfieldmentioning
confidence: 99%
See 3 more Smart Citations